Optimization of extraction parameters of total phenolic compounds from Henna (Lawsonia inermis) Leaves - D.B. Uma,; C.W. Ho,; W.M. Wan Aida, (Universiti Kebangsaan Malaysia, 2010)
Response surface methodology (RSM) in conjunction with central composite rotatable design (CCRD) was performed in the present study to optimize the extraction parameters for assessing maximum yield of total phenolic content (TPC) from henna (Lawsonia inermis) leaves. The range of the independent variables, namely acetone concentration (20-90%, v/v), extraction time (10-90 minutes) and extraction temperature (25-45°C) were identified by a first set of single factor experiments. The actual values of the independent variables coded at five levels were selected based on the results of single factor experiments. The optimum conditions for extraction of TPC were found to be at acetone concentration 48.07%, extraction time 73.78 minutes and extraction temperature 39.57°C. Under these optimized conditions, the experimental maximum yield of TPC was 7203.74 mg GAE/100g DW, which was in close agreement with predicted values, thus indicating the suitability of the models developed and the success of RSM in optimizing the extraction conditions.